Early Prevention of Polycystic Ovarian Syndrome (PCOS) Risk In Children with Growth Hormone Deficiency - Aylicia (PT Kalbe Farma Tbk., 2021)
Polycystic ovarian syndrome (PCOS) is a hormonal disorder and is the leading cause of infertility in women. In 2012, World Health Organization (WHO) stated that around 116 million women around the world were affected by PCOS. The etiology of PCOS has not been fully understood. The most known risk factors are obesity and insulin resistance, usually found in children with growth hormone deficiency (GHD). Growth hormone (GH) therapy can hopefully be the solution to growth disorder and prevent PCOS risks. This article will discuss PCOS and the role of GHD therapy on children in preventing PCOS. Polycystic Ovarian Syndrome (PCOS) adalah gangguan hormonal yang paling umum ditemukan dan merupakan penyebab utama infertilitas pada perempuan. World Health Organization (WHO) pada tahun 2012 menyatakan sekitar 116 juta wanita di seluruh dunia menderita PCOS. Etiologi PCOS belum sepenuhnya dipahami. Namun, faktor risiko yang paling umum diketahui adalah obesitas dan resistensi insulin yang sering didapatkan pada anak-anak dengan growth hormone deficiency (GHD). Terapi growth hormone (GH) diharapkan dapat mengatasi masalah pertumbuhan dan mencegah risiko PCOS. Artikel ini akan membahas PCOS dan peran terapi GHD dalam pencegahan PCOS pada anak.